PELAKSANAAN PEMBELAJARAN MENULIS SURAT DINAS PADA SISWA KELAS VII SMP NEGERI 4 MONTERADO - Monika, Monika; Martono, Martono; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the planning, implementation, and learning outcomes of writing official letters in class VII SMPN 4 Monterado. The research method used was descriptive. Data were taken from two teachers, 21 students of class A and 23 of class B. Research instruments used were Teacher Ability Measurement Tools (APKG I & II), observation guidelines, and a camera. Based on the findings, the lesson plans designed for both classes were appropriate based on the lesson plan components. However, the class B lesson plan was less appropriate in terms of assignment and assessment. The learning implementation in class B was not based on the lesson plans made. Learning outcomes in both classes based on student worksheets reached an average of <70, but the assessment was not optimal due to the absence of an assessment rubric. In class A, the teacher did not carry out an assessment of the aspects of attitude and knowledge, but only the aspect of skills. While in class B, the teacher did not carry out a skill assessment, but only aspects of attitude and knowledge. Therefore, the implementation of the assessment by taking into account the three aspects needs to be reviewed for future improvement.Keywords: Learning Intruction, Official Lerrers.Â